PENGARUH MAHASISWA TERHADAP KEMAMPUAN MENGELOLA KEUANGAN UMKM BERDASARAN SAK EMKM BAROKAH FROZEN FOOD - Tyas Indrayanti; Dian Pramesti Agustina, Tsinta Dewi Aryaningtyas, Andini Putri Bandiah, Isnani Evita Fauziah, Sri Ra (CV. ADIBA AISHA AMIRA, 2024)
The Financial Accounting 2 course is a skill course and a continuation of the Introduction to Accounting course. The Financial Accounting 2 course will study equity and liability material. Financial information has the function of knowing a person's financial condition during a certain period in financial reports. Every MSME has the right to make financial reports that are accurate and comply with accounting standards. Research aimed at assisting MSME entrepreneurs in preparing financial reports according to applicable standards. This research was carried out at the Barokah Frozen Food UMKM in Nginden V A, Surabaya, which has not yet formulated financial reports in accordance with SAK EMKM (Financial Accounting Standards for Micro, Small and Medium Entities). Qualitative descriptive methods are used in observation, interviews and documentation. The factor that causes financial recording at Barokah Frozen Food to not work is due to a lack of understanding of financial reports. This research aims to determine the obstacles that occur in MSMEs in formulating financial reports according to the accounting standards that apply to SAK EMKM (Financial Accounting Standards for Micro, Small and Medium Entities).